The Euro-American influence on indigenous whaling in Alaska - Zdražil, Jakub (2006)
Thesis examines the impact of western civilization on the indigenous people of the western Alaskan region. Within the overview of historical development of indigenous whaling in Alaska (that serves as a basis for further reasoning), the period of commercial whaling is focused on to underline the radical cultural changes in the thousand-year history of indigenous people of Alaska. The second in importance is the second half of the twentieth century, during which the fundamental shift in the perception of native whaling occurred. Historical as well as socio-cultural and technological views have been used to provide a self-contained analysis of undergone changes.